2016
DOI: 10.1021/acs.cgd.6b00858
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Ga Droplet Wetting, Morphology, and Pinholes on the Orientation of GaAs Nanowires

Abstract: Ga-catalyzed growth of GaAs nanowires on Si is a candidate process for achieving seamless III/V integration on IV. In this framework, the nature of silicon's surface oxide is known to have a strong influence on nanowire growth and orientation and therefore important for GaAs nanowire technologies. We show that the chemistry and morphology of the silicon oxide film controls liquid Ga nucleation position and shape; these determine GaAs nanowire growth morphology. We calculate the energies of formation of Ga drop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 36 publications
5
41
0
Order By: Relevance
“…With respect to the oxide thickness we find that a thicker oxide favors the formation of tilted nanowires. This result can be compared to the work by Matteini et al, 24 where a thicker native silicon oxide was found to favor spilling of gallium droplets and therefore nucleation of tilted nanowires. Whether or not the explanation of the surface energy also applies in our case is subject to further investigation.…”
Section: ■ Results and Discussionsupporting
confidence: 56%
“…With respect to the oxide thickness we find that a thicker oxide favors the formation of tilted nanowires. This result can be compared to the work by Matteini et al, 24 where a thicker native silicon oxide was found to favor spilling of gallium droplets and therefore nucleation of tilted nanowires. Whether or not the explanation of the surface energy also applies in our case is subject to further investigation.…”
Section: ■ Results and Discussionsupporting
confidence: 56%
“…31 Increased oxide thickness or hole density might prevent the appearance of crawling objects. [32][33][34][35] Fig. 2(b) and (c) show the cross-sectional SEM images of another sample in the two perpendicular cleaving directions.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of the NW density with decrease in growth temperature therefore suggests that the reduced desorption of the Ga adatoms from the substrate may balance the reduction in droplet volume to some extent, but it cannot compensate for other effects. These have a deleterious impact on nanowire nucleation 39 . Therefore, we suggest that lowering the substrate temperature to 600 °C results in a reduction in the density of the droplets, which can retain the optimum volume for NW nucleation, leading to uneven 2D growth.…”
Section: Resultsmentioning
confidence: 99%